Rancang Bangun Aplikasi Monitoring Work Order Teknisi Berbasis Web Pada PT. Infomedia Nusantara - Andrey Agung Samui; Bagas Setiyaki Wicaksono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Monitoring system design at PT. Infomedia Nusantara is intended to make it easier for office staff to monitor technicians, because currently the monitoring and reporting process only uses chat, which causes office staff to spend more time. In addition, there is no need for office staff to ask about the progress made by technicians in the field, because office staff can see it on the web site. And for the admin, it also helps make it easier to manage reports every month. In the design apply Agile method as the method used. This research produces a web site monitoring system at PT. Infomedia Nusantara which makes it easier for office workers to monitor the work of technicians, know the presence of technicians, and also make it easier for the admin to manage reports.